Hydrodynamic Force Comparison on Multi-Hull, Monohull and Single-to-Twin After Ship Hull (STASH) Based on Seakeeping Criteria - Gde A Prabhawatya Poundra; Bagus Kusuma Aditya; Sinung Widiyanto (IPTEK The Journal of Engineering, 2024)
An investigation into the hydrodynamic force and seakeeping of single-to-twin after ship hull (STASH) and multi-hull geometry was done successfully. STASH is characterized by its monohull-shaped design in the fore part and twin hull in the rear part creating unique performance, especially seakeeping which being the focus study to provide seaworthiness. The method of accomplishing this study was through computer simulation using Maxsurf: Motion for seakeeping and hydrodynamic force analysis. The overall results were compared with published data and mathematical models for validation purposes. The results are believed to be useful for the development of the ship design and performance.